Assessing Strategies of Performing Critical Thinking in an Argumentative Essay - Yamin, Moh.; Aulia, Vivi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This study aims to assess strategies of performing critical thinking in an argumentative essay to a number of selected scientific articles. The method used is descriptive with a qualitative approach with systematic literature review. Manual coding is used to map and get the relevant data to tabulate; content analysis is used to analyze the data. The result study says that critical thinking used in writing argumentative essay is effected by the experience of writing, background of knowledge of the author, and the awareness to respond to the issue. Consequently, the sharpness of the argumentative essay with critical thinking for each author is different.